Diseño geotécnico de cimentaciones aplicando factores de carga y resistencia. (LRFD) (2015)
In the present work, the geotechnical design of foundations was deepened by applying load and resistance factors (LRFD). This design method has been widely developed internationally by AASHTO and Eurocode. The method is based on the application of reliability analysis. The Colombian code of seismic design of bridges of the year 1995 (CCDSP-95), allows the application of the design procedures indicated by the AASHTO, but since there is no knowledge of the fundamentals on which the method is supported, it is has applied inadequately. The development of this work encompasses activities such as: historical analysis of the concept and evolution of the safety factor, design approaches, methods of calibration of the resistance factors, application examples, approach of future lines of research and / or deepening. The concept of the safety factor has evolved since 1729 when it is considered that the concept was proposed by Belidor. Subsequently, Coulomb in 1773 formulated values ​​for the safety factor for the capacity and overturning of containment structures. The concept of the safety factor evolved under two perspectives, the first one raised by Terzaghi and Peck who raised the management of the safety factor through a total safety factor, the second approach was raised by Taylor to indicate that separate factors were required for cohesion and friction. The concept of independent factors for friction cohesion gave rise to the management of partial factors for load and resistance. This approach developed under a probability and statistical perspective corresponds to the reliability analysis of the LRFD method. The design methods are linked to the management of the safety factor and three concepts were studied; the first corresponds to the design for admissible stresses in which the imposed loads are compared with the ultimate strength of the soil divided by a safety factor, the second approach is to compare the loads of the system amplified by load factors and compare them with the resistance of the load. soil affected by a reduction factor, these factors are evaluated in a deterministic way, the third approach corresponds to the application of load amplification factors and reduction of resistance but obtained from a statistical analysis of the variables involved. Finally, some calibration methods were applied to determine resistance reduction factors from geotechnical data (field and laboratory tests) and the amplification factors proposed in the Colombian standards.